PERLINDUNGAN HUKUM BAGI NARAPIDANA RENTAN DI INDONESIA - Subroto, Mitro; Windy, Wempy Yahya (Ensiklopedia Sosial Review, 2024)
Correctional Institutions (Lapas) in Indonesia are still in the public spotlight due to various problems, one of which is related to legal protection for vulnerable inmates. Vulnerable groups in Lapas consist of female inmates, children, the elderly, persons with disabilities, inmates with life sentences and convicts with the death penalty. This study aims to determine the legal arrangements in Indonesia in ensuring the protection of the rights of vulnerable inmate groups, especially in the child category. The research method used is normative research by examining the relevant laws and regulations. The results showed that there are several regulations that form the legal basis for protecting the rights of child inmates, such as Law Number 3 of 1997, Law Number 11 of 2012, and Law Number 22 of 2022. However, these regulations have not been fully able to guarantee legal certainty for the protection of child inmates. The obstacles experienced include the lack of special food and special resting places for elderly inmates.KeywordsLegal Protection; Vulnerable Inmates; Child Inmates; Elderly Inmates; Human Rights